ADVERTISEMENTS IN THE CINEMA STARTING FROM THE MID 20TH CENTURY - Rhady, Wesam Fhadel (ALBAHITH ALALAMI, 2005)
At the time when many important political events and evolutions took place, the cinema has been pretty active, and witnessed the historical events before and after the two world wars and the cold war. During the first half of the 20th century, the cinema had great interest from the major countries and their politicians, as well as the commercial turnout of large companies to invest in that field for the profits. In the beginning of the 20th century, the major powers like the Soviet Union, the United States, Germany, Italy, England, and France started to compete in the development of their film industry and the investment of the new medium and the transformation of some famous works of fiction into films that perpetuate their cultural and intellectual heritage, But it went beyond the creative, literary and artistic aspects of the film industry when these countries began to have direct control and provide government support to their film companies to encourage them to produce films dealing with issues that are consistent with the nature of the stage and political trends prevailing in the meantime. Going back to the 20s and 30s of the 20th century, we can find several statements by politicians such as Lenin, Mussolini, Hitler and Goebbels persisting on the importance of cinema and control of its industry, and to point out to the danger of the emerging means in the fields of politics, propaganda and media.